2009
DOI: 10.1093/esr/jcn076
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Help and Care in Europe

Abstract: In Europe, on average, three times as many adult children occasionally help their parents with the housekeeping than do provide regular physical care. This is not surprising, considering the great differences between these two types of support. Care follows needs, whereas help tends to be given sporadically when one has the opportunity. In the familial welfare states in Southern Europe, where little professional support is available, provision of care by children is more likely-whereas parents in the north are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
288
4
47

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(353 citation statements)
references
References 33 publications
14
288
4
47
Order By: Relevance
“…Although marriage and the nuclear family have declined over the past decades (OECD 2012), parents and adult children still support each other over the life course (e.g. Bengtson 2001;Silverstein et al 1997;Brandt et al 2009). Older parents support their children when the latter establish families, especially by looking after the grandchildren.…”
Section: Introductionmentioning
confidence: 99%
“…Although marriage and the nuclear family have declined over the past decades (OECD 2012), parents and adult children still support each other over the life course (e.g. Bengtson 2001;Silverstein et al 1997;Brandt et al 2009). Older parents support their children when the latter establish families, especially by looking after the grandchildren.…”
Section: Introductionmentioning
confidence: 99%
“…Recent surveys at regional and international levels have highlighted the important role that older people are playing within the European family in terms of family transfers (Harper & Leeson, 2009;Brandt, Haberkern, & Szydik, 2009;Hank, 2009;Hank & Barber, 2009). Most surveys also report a relatively high degree of contact between grandparents and grandchildren, with average physical contact occurring at least once a month, supplemented by other forms of communication (Age Concern, 1997, 1998Arthur, Snape, & Dench, 2003;Dench et al, 1999;Leeson, 2004;Harper, 2003Smith, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Finch and Mason (1993) have described in detail how family responsibilities are negotiated over time, and how some children in the family end up committing themselves to taking care of parents, while others do not. Earlier research has demonstrated, perhaps contrary to common belief, that having fewer siblings increases the probability of providing help (Spitze and Logan 1991;Stuifbergen et al 2008;Brandt, Haberkern, and Szydlik 2009) and keeping in touch with parents (van Gaalen, Dykstra, and Flap 2008). Having many siblings may make it easier to avoid care responsibility by passing it on to brothers, and in particular to sisters.…”
Section: More Children -More Care?mentioning
confidence: 88%